The vibration analysis model of pipeline under the action of gas pressure pulsation coupling. (August 2016) - Tian, Jialin; Yuan, Changfu; Yang, Lin; Wu, Chunming; Liu, Gang; Yang, Zhi
Abstract: Pipeline vibration is the main factor that makes pipeline system can't work properly. And the pressure pulsation of the air flow is one of the important factors, which causes the gas pipeline vibration. In order to further understand the influence of the pressure pulsation on the pipeline system vibration, the analysis model and calculation method of the pressure pulsation and pipe coupling interaction are established. Taking transferring matrix method to calculate the natural frequency of gas column, and using the stiffness matrix method to obtain the pressure pulsation. According to the interaction force between the pressure pulsation and the pipeline wall, the equation of forced vibration of pipeline is established, which can obtain the variation trends of vibration displacement and velocity of pipeline system. Using field test data to verify the theoretical calculation results, the results of the calculated values and test values are within error limits. The results can provide a theoretical basis for the safety evaluation of oil and gas pipeline, and provide a reference for the pipeline mechanical properties research. Highlights: Establishing the analysis model and calculation method of the pressure pulsation and pipe coupling interaction. Taking transferring matrix method to calculate the natural frequency of gas column. Using the stiffness matrix method to obtain the pressure pulsation. By field test data, the results of the calculated values and test values are within error limits.